FDI stocks are a biased measure of MNE affiliate activity: A response - Mira Wilkins (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
The term FDI is often used loosely. This Perspective explains the historical genesis of that loose use and the relationship between FDI and MNEs. FDI stock is one of many measures of MNE activities, but has advantage over the others, since we have long, albeit imperfect, series on FDI stock. Handled with care, along with a keen recognition of the data limitations, FDI continues to serve as one excellent indicator of MNE activities.
Keywords: 330